2019
DOI: 10.3171/2017.12.jns171150
|View full text |Cite
|
Sign up to set email alerts
|

A new model of experimental hemispherotomy in young adult Rattus norvegicus: a neural tract tracing and SPECT in vivo study

Abstract: OBJECTIVEThe objective of this study was to describe a new experimental model of hemispherotomy performed on laboratory animals.METHODSTwenty-six male young adult Wistar rats were distributed into two groups (surgery and control). The nonfluorescent anterograde neurotracer biotinylated dextran amine (BDA; 10,000 MW) was microinjected into the motor cortex area (M1) according to The Rat Brain i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 52 publications
(69 reference statements)
0
1
0
Order By: Relevance
“…Indeed, the neural tract tracings performed in this study demonstrated connections between the IC and both dorsal (deep layers of the superior colliculus and dorsal columns of the periaqueductal gray matter) and ventral (SNpl) midbrain structures. Both the deep layers of the superior colliculus and the dorsolateral columns of the periaqueductal gray matter are interconnected ( Ribeiro et al, 2005 ; Freitas et al, 2005 ), receive inputs from the substantia nigra ( Eichenberger et al, 2002 ; Ribeiro et al, 2005 ; Castellan-Baldan et al, 2006 ), a ventral midbrain structure also connected to the neostriatum ( Castellan-Baldan et al, 2006 ; Matias et al, 2019 ), and send projections to the deep midbrain and pontine reticular formation ( Coimbra et al, 2006 ). These former areas also include the mesencephalic locomotor region (MLR; Sébille et al, 2017 ), an important midbrain structure implicated in commands for movement initiation and gait selection ( Jordan et al, 2008 ; Takakusaki, et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the neural tract tracings performed in this study demonstrated connections between the IC and both dorsal (deep layers of the superior colliculus and dorsal columns of the periaqueductal gray matter) and ventral (SNpl) midbrain structures. Both the deep layers of the superior colliculus and the dorsolateral columns of the periaqueductal gray matter are interconnected ( Ribeiro et al, 2005 ; Freitas et al, 2005 ), receive inputs from the substantia nigra ( Eichenberger et al, 2002 ; Ribeiro et al, 2005 ; Castellan-Baldan et al, 2006 ), a ventral midbrain structure also connected to the neostriatum ( Castellan-Baldan et al, 2006 ; Matias et al, 2019 ), and send projections to the deep midbrain and pontine reticular formation ( Coimbra et al, 2006 ). These former areas also include the mesencephalic locomotor region (MLR; Sébille et al, 2017 ), an important midbrain structure implicated in commands for movement initiation and gait selection ( Jordan et al, 2008 ; Takakusaki, et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%